Decolonising sambo : transculturation, fungibility and black and people of colour futurity - Tate, Shirley Anne (Critical mixed race studies., 2020)
"Using a Black decolonial feminist approach, this book deconstructs 'the white sambo psyche' of white European settler colonialism, which classifies the colonised and enslaved into 'sambo': a category of racial subjection and utter negation which is now so normalized that we are inured to it. Drawing on voyages both real and metaphorical to places such as Australia, South Africa, Jamaica, the Dutch West Indies, and the UK, Decolonizing Sambo positions itself amongst the global entanglements of white European settler colonialism, racial capitalism and contemporary culture. This cultural analysis analyses archival data, artefacts, commemorative spaces, films, children's books, and sweets to show sambo's genealogy, transculturation, fungibility, and continuation in contemporary racialising assemblages. As we continue to live in an era of 'samboification', this book provides scholars and students with the materials to start thinking about sambo as an (un)known part of colonialism and explore 'post-race' racism within which professions of sincere love for the racialised other are an active aspect of (post) colonial states' self-deception about being 'post-race'."--